ILLOCUTIONARY SPEECH ACTS IN FRIDAY SERMONS AT MASJID AL-HARAM: TINDAK TUTUR ILOKUSI DALAM KHOTBAH JUMAT DI MASJIDIL HARAM - Shofia Rosyida; Muhammad Yunus Anis (Program Studi Bahasa dan Sastra Arab STIABI Riyadul 'Ulum, 2025)
Friday sermons are an important act of worship in Islam that not only convey religious teachings but also contain illocutionary speech acts. This study aims to examine the types of illocutionary speech acts found in the Friday sermons of Sheikh Bandar Balilah and Sheikh Su’ud Asy-Syuraim at the Grand Mosque (Masjid al-Haram). The research employs a descriptive qualitative method, with data sourced from transcripts of the sermons and their translations, obtained from the YouTube channels Fawaid Haramain and Khutbah Al-Haramain. Data collection techniques include observation, listening, and note-taking. The results show that in Sheikh Bandar Balilah's Friday sermon, a total of 63 illocutionary speech acts were identified. Among these, directive speech acts dominated with 43 occurrences (68%), followed by assertive acts with 10 occurrences (16%), and both expressive and commissive acts with 5 occurrences each (8%). In the Friday sermon delivered by Sheikh Su’ud Asy-Syuraim, 79 illocutionary speech acts were found. These consisted of 32 directive acts (40%), 26 assertive acts (33%), 17 expressive acts (22%), 3 commissive acts (4%), and 1 declarative act (1%).